Climate tipping point game for Conference of the Parties (COP) delegates - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The game was played with delegates and other stakeholders at the 2018 SBSTA (Bonn) and COP (Katowice). Significant impacts on risk perceptions around climate tipping points were found - paper forthcoming.